Nurse staff Working Hours and their exposure to Occupational Health Hazard at Saudi Arabia Hospitals: cross sectional study (The Review of Diabetic Studies, 2024)
Low basic staffing levels generally, challenges finding and retaining qualified employees, and the absence of replacements in the event of sick leave could all contribute to the shortage of qualified staffing. Accidents and malpractice are typically attributed to human error, but in recent years, there has been a greater awareness of organizational and structural factors, such as the work environment, workload, shift patterns, qualified and adequate staffing, and organizational structure Aim of the Study: The current study aims to determine the relationship between hospital staff nurses' working hours and occupational health hazards. Subject and Method: A descriptive correlation, quantitative, cross sectional  research design was utilized to achieve the aim of the current research. Settings: Nurses employed in all government hospitals in and near Hail, Saudi Arabia, including King Khaled Hospital, Hail General Hospital, King Salman Hospital, and Sharaf Hospital, provided the data. Data were gathered by two tools divided as following; Working Hours Questionnaire and Occupational Health Hazards Questionnaire. Finding: 51.2% of staff nurses work 50 hours or more per week, 36.2% work unlimited paid overtime, 41.9% work paid overtime because of a lack of staff, 54.2% work unlimited unpaid overtime, and 54.2% work unpaid overtime because of a lack of staff and excessive workload. Furthermore,  there are positive correlations between health hazards and (the number of working hours you work each week as well as the number of overtime hours you work each week). Conclusion: This study found that over two thirds of staff nurses had high exposure to physical hazards, while one third had low exposure to physical hazards. Additionally, whereas the minority of staff nurses had substantial exposure to biological dangers, the majority had modest exposure. Additionally, this study revealed that the majority of staff nurses had high exposure to both organic and inorganic problems, and that over half had high exposure to psychosocial hazards, while fewer than half had low exposure to psychosocial hazards. Clear and precise job descriptions, flexible work arrangements, equitable treatment, and frequent meetings between managers and staff nurses to address any issues and resolve any hazardous hazards.